Situational Analysis of Climate Change-Agriculture-Gender Inequality Hotspots in Bangladesh - Lecoutere, Els; Akhter, Sadika; Puskur, Ranjitha; Mishra, Avni; Reidpath, Daniel D; Rahman, Aminur; Singaraju, Niyati; Hanifi, Manzoor A; Kamruzzaman, Mohammed (2023)
The goal of the situational analysis was to validate a prior geospatial mapping of subnational hotspots in Bangladesh, where women in agricultural and food systems are at the most risk of the impacts of gender inequality and climate change. The study identifies areas where decision makers in climate change investments should prioritize to target.